Representation of the Sandwich Generation in Home Sweet Loan: Implications for Social Education and Life Literacy - Bunga Nur Afidah Arif; Thriwaty Arsal (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines the representation of the sandwich generation in the film Home Sweet Loan through the lens of social construction theory and its relevance to social education. Using a descriptive qualitative design, the study analyzes scenes, dialogues, and narrative elements through repeated observation and thematic coding. The findings show four interconnected themes: economic pressure, role conflict, unequal family responsibility, and identity negotiation. These themes indicate that the sandwich generation is not merely an individual condition, but a socially constructed reality shaped by family expectations, collectivist values, and unequal power relations. The film also demonstrates educational potential as a contextual medium for teaching social literacy, empathy, and critical thinking about family dynamics in contemporary society. This study contributes a social-educational perspective to film analysis and offers a conceptual basis for using audiovisual media to discuss intergenerational responsibility in learning contexts. By linking media representation and classroom reflection, the study extends communication studies into practical pedagogical discussion.